Asymptotic formulas for Dirichlet boundary value problems - (:unkn) unknown (AKADEMIAI KIADO, 2005)
In this article we obtain asymptotic formulas of arbitrary order for eigenfunctions and eigenvalues of the nonselfadjoint Sturm-Liouville operators with Dirichlet boundary conditions, when the potential is a summable function. Then using these we compute the main part of the eigenvalues in special cases.
Keywords: asymptotic formulas; Sturm-Liouville operators